(3GdCSFdI GdcHQis - (3ZGRj Hf YHO GdQMef(B, (3GdbUjHjs ((3HjQhJ(B:s (3OGQ GdaGQS ddfTQ hGdJhRjY(B,s, 2006)
(3GdJfejI,deGPG?(B-(3GdJfejI,def?(B-(3GdJfejI,eGPG?(B-(3GdJfejI,cja(B-(3GdJfejI GdeaJGM GdSQjs
(3HHdjhZQGajG(B:(3U(B.127-134s
Keywords: (3GdJfejI GdGbJUGOjIs